SYMPTOMATOLOGY OF FEMALE PATIENTS ATTENDING MOBILE MEDICAL CLINICS IN A RURAL BLOCK IN TAMILNADU - M, Logaraj; S, Sathiyanarayanan; R, Balaji (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of the study were to find out the prevalence of symptoms not elsewhere classifiedâ€ under the International Classification of Diseases, Tenth Revision, Clinical Modification among the female patients attending mobile medical clinics. Methods: A cross-sectional study was carried out among 7,124 female patients who attended weekly mobile medical clinics in a rural block in Tamil Nadu. Sociodemographic variables, symptomatology, patient history, and clinical examination details were collected using a pre-tested structured questionnaire. Results: The five common symptoms affecting the study population were myalgia (18.3%), nasal congestion (13.6%), headache (13.1%), lumbar pain (12.5%), and knee pain (9.3%). The systems commonly affected among the female patients were in the order of general symptoms and signs (R50-R69), circulatory and respiratory systems (R00-R09), and Nervous and Musculoskeletal Systems (R25-R29). In the age group of 10â€“19 years and 20â€“39 years, the most common symptom was headache (25.2% and 18.8%, respectively). In the age group of 40â€“59 years and 60 years and above, it was myalgia (24.2% and 32.3%, respectively). Conclusion: As pain being most common symptoms, an appropriate strategy and guidelines have to be developed to manage the problem of pain at primary care level.